Exploring the impact of peer review in electrical engineering courses. - Boluda-Ruiz, Rubén; Campo-Valera, María; Moreno-González, Inés (IATED, 2024)
The use of peer review in university students enrolled in STEM (Science, Technology, Engineering, and Mathematics) degrees emerges as an ever-evolving educational strategy. This approach is justified not only by its solid theoretical foundation, but also by its capacity to foster critical evaluation skills among students. In the STEM university context, peer review offers tangible benefits. This study explores the impact of employing peer review as an educational tool in courses within the Degree of Electrical Engineering at the University of Málaga, defining specific rubrics and ensuring non-influence on students' final grades. The findings indicate a positive evaluation from students, with averages reflecting a favorable perception of the quality of the evaluation produced.
La editorial da permiso para depositar en abierto en RIUMA. Correo RIUMA 07/04/2025
Keywords: Investigación activa en educación; Electrotecnia - Estudio y enseñanza superior; Peer review; Evaluation; Learning; Electrical Engineering